Bonomyces pseudoarnoldii (Biannulariaceae, Agaricales), a new species from China revealed by morphology, and multilocus phylogenetic analysis - Mao, Ning; Lv, Jing-Chong; Zhao, Tao-Yu; Fan, Li (Phytotaxa, 2022)
Bonomyces pseudoarnoldii is the name proposed for a new species found in north China, based on both morphological and molecular data. Phylogenetic analyses on sequence data from five different loci (ITS, SSU, LSU, tef1 and rpb2) support that this species belongs to the genus Bonomyces. Bonomyces pseudoarnoldii resembles other species of Bonomyces in its small reddish brown to pale orange pileus covered with finely to coarsely fibrillose or minute squamules, and pale white to reddish brown stipe with longitudinal fibrils. The new species is presented with illustrated description, molecular data, and comparison to related or similar species. We provide a key to the known species of Bonomyces in the world.